2017
DOI: 10.1007/s00431-017-3029-2
|View full text |Cite
|
Sign up to set email alerts
|

Urinary potassium to urinary potassium plus sodium ratio can accurately identify hypovolemia in nephrotic syndrome: a provisional study

Abstract: A subgroup of patients in nephrotic syndrome has a decrease in glomerular filtration, apparently related to hypovolemia which likely can be detected by a urinary potassium to potassium plus sodium ratio > 0.5-0.6 suggesting benefit of albumin infusion in this subgroup. What is Known: • Volume status can be difficult to assess based on clinical parameters in nephrotic syndrome, and albumin infusion can be associated with development of pulmonary edema and fluid overload in these patients. What is New: • Urinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…11 Hence, it did Keenswijk et al, who studied the K index as an indicator of hypovolemia in 44 children with nephrotic syndrome. 12 Iyenger et al, found that 50% of steroid responsive children and 36% of steroid non-responders had low K index suggestive of hypervolemia. 2 This may suggest that steroid resistance in nephrotic syndrome may favor hypovolemia.…”
Section: Discussionmentioning
confidence: 99%
“…11 Hence, it did Keenswijk et al, who studied the K index as an indicator of hypovolemia in 44 children with nephrotic syndrome. 12 Iyenger et al, found that 50% of steroid responsive children and 36% of steroid non-responders had low K index suggestive of hypervolemia. 2 This may suggest that steroid resistance in nephrotic syndrome may favor hypovolemia.…”
Section: Discussionmentioning
confidence: 99%
“…The clinically impractical gold standard techniques of bromide or deuteriated water dilution have been supplanted in humans by indirect methods such as bioimpedance analysis and was therefore not performed in our pilot study [ 23 ]. Similarly, the urinary potassium/ (potassium + sodium) ratio has been suggested as a surrogate of hypovolemia in nephrotic children to replace the dilution methods with radioactively labeled red blood cells or proteins [ 24 ]. To date, the validity of this method has not been evaluated in companion animals.…”
Section: Discussionmentioning
confidence: 99%
“…Typical values for pre-renal azotemia have not been precisely determined; in hypoperfusion, typical values are below 1 mmol/mmol [6]. The ratio of the urine potassium level to the sum of potassium and sodium is a recently described new parameter useful in testing for hypovolemia in nephrotic syndrome [21].…”
Section: Discussionmentioning
confidence: 99%